Managing technology-related disruptions and vulnerabilities in highly automated warehouse systems : an integrative review and research agenda - Rodríguez-García, Miguel; Kembro, Joakim Hans ; 0000-0002-0705-3987; Betts, Kellen; Ponce-Cueto, Eva (International Journal of Production Research, 2025)
Recent technological developments in warehousing have introduced new risks. This paper presents an integrative review that combines insights from highly automated warehouse systems (HAWS) and risk management, providing a comprehensive understanding of technology-related warehouse disruptions and vulnerabilities. We identify five major disruptions that can affect HAWS: cyberattacks, technology sabotage, technology failures, power and network outages, and human-machine interaction issues. Moreover, we identify 48 technology-related vulnerabilities across all disruptions. In particular, HAWS have become vulnerable to cyberattacks due to the increasing number of warehouse technology suppliers, greater complexity of multi-robot networks such as AMRs, reliance on cloud-based systems, and cascading effect of cyberattacks due to higher levels of interconnectivity in HAWS networks. Our review also shows that risk management strategies in HAWS are unevenly covered in the literature. In response, we propose a research agenda with 17 pathways aimed at enhancing prevention, detection, mitigation, and recovery strategies for HAWS. Managers also benefit from the identified disruptions and vulnerabilities, as they serve as a reference point for understanding their specific technology-related risks in HAWS. In addition, managers can use our review of current risk management practices as a benchmark and our research agenda to think about areas that they could develop further.
Keywords: cybersecurity in warehousing; Highly automated warehouse systems (HAWS); integrative literature review; supply chain risk management; technology-related disruptions; vulnerability assessment